Evaluation of Supply Chain Management Performance at MSMEs using the SCOR Method - Ramadheena, Felia Anjani; Zhafari, Muhammad; Aini, Qurrotul (INTENSIF: Jurnal Ilmiah Penelitian dan Penerapan Teknologi Sistem Informasi, 2020)
The development of the industrial world that accelerates the growth of competition between businesses. It causes the need for activities or efforts to increase the selling power of the company or organization. One of them is by evaluating the level of performance in the supply chain at SME Tosuka Coffee. It is done to determine the level of current business conditions and to know what elements have good potential in business development and what components need to be improved. This evaluation uses the SCOR method in assessing supply chain performance. The assessment with SCOR is based on Tosuka's current condition. The results of this study state that the final value of the SCOR calculation yields a figure of 86.24, which means that Tosuka Coffee's business is at a good level, especially in the Plan process that receives the highest value with Responsiveness dimension and is followed by the Return process with the Reliability dimension. However, Tosuka Coffee is recommended to make performance improvements in the Make, Source, and Deliver processes because it produces a relatively low value. With the evaluation, it is expected that Tosuka Coffee can improve supply chain performance in the future.